The square root of (7+3 root 5)(7-3 root 5) is
Answers
Answered by
17
HELLO DEAR,
![\sqrt{(7 + 3 \sqrt{5})(7 - 3 \sqrt{5} )} \\ \\ = > \sqrt{49 - 45} = \sqrt{4} = 2 \sqrt{(7 + 3 \sqrt{5})(7 - 3 \sqrt{5} )} \\ \\ = > \sqrt{49 - 45} = \sqrt{4} = 2](https://tex.z-dn.net/?f=+%5Csqrt%7B%287+%2B+3+%5Csqrt%7B5%7D%29%287+-+3+%5Csqrt%7B5%7D++%29%7D++%5C%5C+++%5C%5C+%3D++%26gt%3B++%5Csqrt%7B49+-+45%7D++%3D++%5Csqrt%7B4%7D++%3D+2)
I HOPE ITS HELP YOU DEAR,
THANKS
I HOPE ITS HELP YOU DEAR,
THANKS
Answered by
4
Answer:
plz mark me as brainlist and thank me
Attachments:
![](https://hi-static.z-dn.net/files/d57/98a5dfeef89fe7ff5ef28ab7baeb87a9.jpg)
Similar questions
Computer Science,
9 months ago
Math,
9 months ago
India Languages,
9 months ago
Computer Science,
1 year ago
Sociology,
1 year ago
English,
1 year ago